Analisis Potensi Ocean Thermal Energy Conversion (OTEC) di Wilayah Geografis Laut Barat Sumatera - Parsaulian, Kevin Sahat; Amir, Afif Asykar; Gunawan, Andit Zelly (Metta : Jurnal Ilmu Multidisiplin, 2025)
Ocean Thermal Energy Conversion (OTEC) is an emerging marine renewable energy technology that exploits the natural temperature gradient between warm surface seawater and cold deep-sea water to generate electricity. This thermal energy potential is especially significant in tropical regions such as Indonesia, where oceanographic conditions are favorable. The West Sumatra Sea, bordering the Indian Ocean, is identified as a promising site for OTEC development due to its consistently high surface temperatures and considerable bathymetric depth. This study aims to assess the monthly vertical and horizontal temperature distributions, evaluate the seasonal variations, and calculate the theoretical efficiency of OTEC systems in the region. Ocean temperature data were sourced from the Copernicus Marine Environment Monitoring Service (CMEMS) and analyzed using Ocean Data View (ODV) software. Results indicate that surface water temperatures range between 29.3°C and 30.57°C, while deep-sea temperatures at 600 meters depth remain around 8.96°C. The average vertical temperature difference (∆T) throughout the year is approximately 21°C, satisfying the minimum threshold for OTEC viability. The thermocline layer is located between 40 and 77 meters, while deep water extends beyond 900 meters. The calculated average Carnot efficiency is 0.70, indicating a strong theoretical potential for energy conversion. Seasonal analysis also shows stable ∆T values during transitional monsoon periods, suggesting year-round operational feasibility. These findings confirm that the oceanographic characteristics of the West Sumatra Sea support the sustainable development of OTEC technology and highlight its strategic potential in contributing to Indonesia’s renewable energy transition.